Client-provider interactions in provider-initiated and voluntary HIV counseling and testing services in Uganda - Wanyenze, Rhoda K.; Kyaddondo, David; Kinsman, John; Makumbi, Fredrick; Colebunders, Robert; Hardon, Anita (BMC Health Services Research, 2013)
Provider-initiated HIV testing and counselling (PITC) is based on information-giving while voluntary counselling and testing (VCT) includes individualised client-centered counseling. It is not known if the providerclient experiences, perceptions and client satisfaction with the information provided differs in the two approaches. Methods: In 2008, we conducted structured interviews with 627 individuals in Uganda; 301 tested through PITC and 326 through voluntary counselling and testing (VCT). We compared client experiences and perceptions based on the essential elements of consent, confidentiality, counseling, and referral for follow-up care. We conducted multivariate analysis for predictors of reporting information or counselling as sufficient. Results: In VCT, 96.6% (282) said they were asked for consent compared to 91.3% (198) in PITC (P = 0.01). About the information provided, 92.0% (286) in VCT found it sufficient compared to 78.7% (221) in PITC (P = <0.01). In VCT 79.9% (246) thought their results were kept confidential compared to 71.7% (200) in PITC (P = 0.02). Eighty percent (64) of HIV infected VCT clients said they were referred for follow-up care versus 87.3% (48) in PITC (p = 0.2). Predictors of perceived adequacy of information in PITC included an opportunity to ask questions (adj.RR 1.76, CI 1.41, 2.18) and expecting the test results received (adj.RR 1.18, CI 1.06, 1.33). For VCT significant factors included being given an opportunity to ask questions (adj.RR 1.62, CI 1.00, 2.60) and 3+ prior times tested, (adj.RR 1.05, CI 1.00, 1.09).
Keywords: Provider-initiated HIV testing; HIV counselling